Large-scale magnetic field oscillations and their effects on modulating energetic electron precipitation - Qin, Murong; Li, Wen; Ma, Qianli; Shen, Xiao-Chen; Woodger, Leslie; Millan, Robyn; Angelopoulos, Vassilis (Frontiers in Astronomy and Space Sciences, 2024)
In this study, we present simultaneous multi-point observations of magnetospheric oscillations on a time scale of tens of minutes (forced-breathing mode) and modulated whistler-mode chorus waves, associated with concurrent energetic electron precipitation observed through enhanced BARREL Xrays. Similar fluctuations are observed in X-ray signatures and the compressional component of magnetic oscillations, spanning from ~9 to 12 h in MLT and 5 to 11 in L shell. Such magnetospheric oscillations covering an extensive region in the pre-noon sector have been suggested to play a potential role in precipitating energetic electrons by either wave scattering or loss cone modulation, showing a high correlation with the enhancement in X-rays. In this event, the correlation coefficients between chorus waves (smoothed over 8 min), ambient magnetic field oscillations and X-rays are high. We perform an in-depth quasi-linear modeling analysis to evaluate the role of magnetic field oscillations in modulating energetic electron precipitation in the Earth's magnetosphere through modulating whistler-mode chorus wave amplitude, resonance condition between chorus waves and electrons, as well as loss cone size. Model results further show that the modulation of chorus wave amplitude plays a dominant role in modulating the electron precipitation. However, the effect of the modulation in the resonant energy between chorus waves and energetic electrons due to the background magnetic field oscillations cannot be neglected. The bounce loss cone modulation, affected by the magnetic oscillations, has little influence on the electron precipitation modulation. Our results show that the low frequency magnetospheric oscillations could play a significant role in modulating the electron precipitation through modulating chorus wave intensity and the resonant energy between chorus waves and electron.